"Io ho voluto scrivere tutto quel che me passa per la mente". Le lettere di Giulia Gonzaga (Quaderni di Gargnano, 2018)
The almost entirely unpublished collection of Giulia Gonzaga’s letters tells not only the story of one woman’s private life but, as is often the case with female correspondence, interweaves personal, public and institutional themes. These are ‘domestic' letters in which concerns about the household, children, nephews and nieces, are entwined with discussions about the difficulties of government, the petty personal ambitions of the power-hungry, and the defence of the family blood line. A gentlewoman who was perhaps better known for her beauty than her culture, Giulia Gonzaga is a lively witness of a society at the centre of an unprecedented political and religious crisis. The hundreds of mostly handwritten letters chronicle diverse moments from the history of sixteenth-century Italy, sometimes dealing at length with political and religious affairs from around 1520 to 1565. Giulia Gonzaga was at the centre of a complicated aristocratic order whose imperial ambitions and mode of governance sometimes came into direct conflict with the papacy, which had its own designs on power. Nobles such as Giulia Gonzaga were therefore both tolerant of and curious about new religious thinking. Together with her “spiritual” friends and supporters of ecclesiastic reform, she contributed to the effort to shift the religious policy of the Church of Rome. She gives voice to dissent and fears, and laments the defeats that the reformists suffered at the hands of the Roman Inquisition.
Keywords: Giulia Gonzaga; collection of letters; Inquisition